Particulate matter concentrations during desert dust outbreaks and daily mortality in Nicosia, Cyprus - Neophytou, Andreas M.; Yiallouros, Panayiotis K.; Kleanthous, Savvas; Pavlou, Pavlos; Pashiardis, Stelios; Dockery, Douglas W.; Laden, Francine; Koutrakis, Petros; Coull, Brent A. (My University, 2013)
Ambient particulate matter (PM) has been shown to have short- and long-term effects on cardiorespiratory mortality and morbidity. Most of the risk is associated with fine PM (PM 2.5); however, recent evidence suggests that desert dust outbreaks are major contributors to coarse PM (PM 10-2.5) and may be associated with adverse health effects. The objective of this study was to investigate the risk of total, cardiovascular and respiratory mortality associated with PM concentrations during desert dust outbreaks. We used a time-series design to investigate the effects of PM 10 on total non-trauma, cardiovascular and respiratory daily mortality in Cyprus, between 1 January 2004 and 31 December 2007. Separate PM 10 effects for non-dust and dust days were fit in generalized additive Poisson models. We found a 2.43% (95% CI: 0.53, 4.37) increase in daily cardiovascular mortality associated with each 10-μg/m 3 increase in PM 10 concentrations on dust days. Associations for total (0.13% increase, 95% CI: -1.03, 1.30) and respiratory mortality (0.79% decrease, 95% CI: -4.69, 3.28) on dust days and all PM 10 and mortality associations on non-dust days were not significant. Although further study of the exact nature of effects across different affected regions during these events is needed, this study suggests adverse cardiovascular effects associated with desert dust events.
Keywords: Cardiovascular mortality; Desert dust; Particulate matter; Time series